Analisis uji daya hambat ekstrak lamun terhadap bakteri patogen di Pulau Bone Batang dan Barrang Lompo, Perairan Spermonde - Nurfadilah, Nurfadilah; Haris, Abdul; Lukman, Muhammad (Tomini Journal of Aquatic Science, 2022)
Seagrass beds are a wealth of marine resources, one of the ecosystems found in coastal areas, capable of producing various secondary metabolites, and seagrasses are known to contain antibacterial active compounds. The purpose of this study was to determine the antibacterial potential of seagrass extracts from Zone I (large and small Lae-lae Island) and Zone II (Gusung Bone Batang and Barrang Lompo) against Staphylococcus aureus and Escherichia coli bacteria. The test method used is the agar diffusion method. The results showed that in Zone I, H. ovalis had an average inhibition of 7.9 mm and E. acoroides had an average inhibition of 8.15 mm, while in Zone II, E. acoroides was 2.5 mm, C Rotundata 1.18 mm, H. uninervis 1.53 mm, T. hemprichii 1.2 mm and H. ovalis 1.73 mm. The highest level of antibacterial activity was in the type of E. acoroides.